Долгоносики рода апион - Apion Hrbst. (Coleoptera, Curculionidae) из Крыма - Солодовникова, В.С. (Вестник зоологии, 1968)
The article deals with the results of ecological and faunistic investigation of the genus Apion Herbst in the Crimea where 65 species of this Curculionidae were found. In the mountainous Crimea about 70% of Apion species were found on moist meadows in the river valleys, on brook banks and lawns of mountain slopes with mesophyllous meadow vegetation. In the Alpine fauna a number of Apion species decreases, the specific mountain species are not observed. Curculionidae of the genus Apion are found on 32 species of herbaceous plants, among which Leguminosae, Compositae, Malvaceae etc. are predominant both on 14 woody and shrubby species. The majority of Apion are oligo-phages. Beetles migrate from herbaceous plants on which their larvae develop to trees and shrubs for additional nutrition. Only on trees two species develop: oligomon.ophages Apion minimum and A. holosericeum. Only one stenotopic species monophage A. artemisiae — is found in fauna (on solonetz soils). Apion fauna on limestones is not so rich as compared with loam fauna. In local fauna the paleoarctic species of the genus (31) predominate, the majority of which are meadow mesophyls (20) and mesophyls of the Mediterranean origin (19); the European species (7) are presented by eurybiontic forms. Three species of hygrophils are found. Apion fauna of the mountainous Crimea as to its composition is very similar to the fauna of forest-steppe and north steppe of the left-bank Ukraine; the fauna of the steppe Crimea have a bent for the fauna of southern subzones of the steppe in the left-bank Ukraine.